MOTIVAŢIA ÎNVĂŢĂRII PE PARCURSUL VIEŢII: PERSPECTIVĂ ANDRAGOGICĂ - USM ADMIN (Moldova State University, 2007)
The motivation of lifelong learning is a process that develops within the course of previous school and life stages/periods. Thus, the andragogical perspective of approaching the motivation for lifelong learning foresees the analysis of now and here and the longitudinal research of the phenomenon. In this article we analyze the interest-attitude and the capacity to learn within the course of life as longitudinal aspects of the motivation for learning.